Enablers and barriers for implementing high-quality hypertension care in a rural primary care setting in Nigeria: perspectives of primary care staff and health insurance managers. Issue 1 (1st December 2016) - Odusola, Aina O.; Stronks, Karien; Hendriks, Marleen E.; Schultsz, Constance; Akande, Tanimola; Osibogun, Akin; Weert, Henk van; Haafkens, Joke A.
Abstract : Background: Hypertension is a highly prevalent risk factor for cardiovascular diseases in sub-Saharan Africa (SSA) that can be modified through timely and long-term treatment in primary care. Objective: We explored perspectives of primary care staff and health insurance managers on enablers and barriers for implementing high-quality hypertension care, in the context of a community-based health insurance programme in rural Nigeria. Design: Qualitative study using semi-structured individual interviews with primary care staff ( n = 11) and health insurance managers ( n =4). Data were analysed using standard qualitative techniques. Results: Both stakeholder groups perceived health insurance as an important facilitator for implementing high-quality hypertension care because it covered costs of care for patients and provided essential resources and incentives to clinics: guidelines, staff training, medications, and diagnostic equipment. Perceived inhibitors included the following: high staff workload; administrative challenges at facilities; discordance between healthcare provider and insurer on how health insurance and provider payment methods work; and insufficient fit between some guideline recommendations and tools for patient education and characteristics/needs of the local patient population. Perceived strategies to address inhibitors included the following: task-shifting; adequate provider payment benchmarking; good provider–insurer relationships; automated administration systems; and tailoring guidelines/patient education. Conclusions: By providing insights into perspectives of primary care providers and health insurance managers, this study offers information on potential strategies for implementing high-quality hypertension care for insured patients in SSA.